A cidade global na obra de Saskia Sassen - Santos, Lucas Quio dos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This monograph is dedicated to the study of the Global City concept propounded for the Dutch and North-american sociologist Saskia Sassen. This is a conceptual formulation that seeks to define the meaning of the contemporary city in the era of economic and political globalization. Through global city, Sassen suggests that the phenomenon of globalization can be perceived through the intersection of national and local spaces with the global space, made by transnational social and political forces since the end of the eighties, particularly, by large corporations. The location of global processes is related to the dynamics of incipient and parcial denationalization of the institutional framework of national states. The denationalization logic reorients the national-economic policy to achieve demands imposed by global capital and promotes the breakdown of the relationship between power and politics that characterized the modern state. The state plays a key role in the global economic system constitution, because it is responsible for the normative production to new forms of economic transactions. However, the state is repositioned in a broader field of power constituted by the new private institutional framework on the global economy. According to Sassen, the necessary conditions for the global economic system existence need to be produced, and global cities are the spaces where this production occurs. Global cities are complex production for global control capability and focus the main institutions that are at the core of wealth creation process and concentration of power. The imposition of the internationalized sector of the urban economy of these cities has profoundly altered the spatial organization of the urban economy, social reproduction structure and the work process in various countries. Besides the economic function, global cities emerge as important areas for a particular form...

Esta monografia é dedicada ao estudo do conceito cidade global proposto pela socióloga holandesa e norte-americana Saskia Sassen. Trata-se de uma formulação conceitual que busca definir o sentido da cidade contemporânea da era da globalização econômica e política. Por meio da cidade global, Sassen propõe que o fenômeno da globalização pode ser apreendido através da intersecção dos espaços locais e nacionais com o espaço global, efetuada pelas forças sociais e políticas transnacionais desde o final da década de oitenta, sobretudo, pelas grandes corporações. A localização de processos globais está relacionada à dinâmica de desnacionalização incipiente e parcial do quadro institucional dos Estados nacionais. A lógica de desnacionalização reorienta a política-econômica nacional à consecução de demandas impostas pelo capital global e promove a ruptura da relação entre poder e política que caracterizou o Estado moderno. O Estado desempenha uma função fundamental na constituição do sistema econômico global, pois é o responsável pela produção normativa para as novas formas de transações econômicas. Entretanto, o Estado é reposicionado em um campo de poder mais amplo constituído pelo novo quadro institucional privado ligado a economia global. Para Sassen, as condições necessárias à existência do sistema econômico global precisam ser produzidas e as cidades globais são os espaços nos quais ocorre essa produção. As cidades globais são complexos de produção para a capacidade de controle global e concentram as principais instituições que estão no núcleo do processo de criação de riqueza e concentração de poder. A imposição do setor internacionalizado sobre a economia urbana dessas cidades tem alterado profundamente a organização espacial da economia urbana, a estrutura de reprodução social e o processo de trabalho nos...
Keywords: Sassen, Saskia; Globalização; Sociologia; Cidades e vilas; Globalization